2020
DOI: 10.1080/20013078.2020.1736935
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the proteomic landscape of extracellular vesicles in prostate cancer by density‐based fractionation of urine

Abstract: Extracellular vesicles (EV) are increasingly being recognized as important vehicles of intercellular communication and promising diagnostic and prognostic biomarkers in cancer. Despite this enormous clinical potential, the plethora of methods to separate EV from biofluids, providing material of highly variable purity, and lacking knowledge regarding methodological repeatability pose a barrier to clinical translation. Urine is considered an ideal proximal fluid for the study of EV in urological cancers due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(189 citation statements)
references
References 90 publications
3
164
0
Order By: Relevance
“…EV pellets are often contaminated by other high abundant molecules (e.g., lipoproteins, protein aggregates, soluble proteins) or proteins that bind non-specifically to the exosomes and can interfere with further MS analysis. A density gradient flotation, such as the sucrose gradient [ 86 ] or the iodixanol (OptiPrepTM) velocity gradient [ 87 , 88 ], can be applied to the differential ultracentrifugation protocol to separate large protein aggregates from exosomes [ 89 ]. Indeed, even if the density of MVs remains unclear, the density of exosomes is about 1.08–1.19 g/mL [ 90 ].…”
Section: Proteomic Methodsmentioning
confidence: 99%
“…EV pellets are often contaminated by other high abundant molecules (e.g., lipoproteins, protein aggregates, soluble proteins) or proteins that bind non-specifically to the exosomes and can interfere with further MS analysis. A density gradient flotation, such as the sucrose gradient [ 86 ] or the iodixanol (OptiPrepTM) velocity gradient [ 87 , 88 ], can be applied to the differential ultracentrifugation protocol to separate large protein aggregates from exosomes [ 89 ]. Indeed, even if the density of MVs remains unclear, the density of exosomes is about 1.08–1.19 g/mL [ 90 ].…”
Section: Proteomic Methodsmentioning
confidence: 99%
“…Therefore, there is an urgent need for additional PCa biomarkers for highly specific monitoring of disease progression and treatment response, including noninvasive exosomal biomarkers from biofluids (e.g., urine and plasma/serum). We reviewed recent proteomic studies of exosomes from urine, plasma/serum, and cell culture media for PCa protein biomarker discovery [ 19 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. A summary of these studies is provided in Table 2 .…”
Section: Exosomal Proteins As Biomarkers For Pca and Bcamentioning
confidence: 99%
“…Gene ontology (GO) cellular component analysis showed that the most abundant proteins that could be derived from EV proteins were plasma membrane proteins (25%). Dhondt et al used UC + DG for isolation of exosome from 48 urine samples including benign, PCa, BCa, and renal cell carcinoma patients, and TEM and NTA for exosome characterization [ 85 ] ( Table 2 ). In total, 3686 proteins were identified with 82% annotated to exosome using GO terms, which demonstrates high-purity exosomes suitable for proteomic analysis.…”
Section: Exosomal Proteins As Biomarkers For Pca and Bcamentioning
confidence: 99%
“…Indeed, using deep sequencing, exosomal DNA was found to have somatic mutations that are commonly found in UBC cells and provide insights into the genetic abnormalities of UBC tumors 66 . Alongside with RNA sequencing of urine-derived EV content, several research groups have conducted proteomic profiling of EVs 67,68,69,75,76,77 . Tumor Associated Calcium Signal Transducer 2 (TACSTD2) was found in high association on the outside of UBC urine isolated EVs and could therefore be used as another potential biomarker for UBC 78 .…”
Section: Molecular Composition Of Urine-derived Evs In Bladder Cancermentioning
confidence: 99%
“…One of the major limitations of previous studies focusing on the molecular characterization of UBC-derived EVs lies in the use of total urinary EVs for RNA and proteomic profiling. Urinary EVs may originate from non-malignant cells of the urinary tract including the prostate, kidneys and the upper urinary tract 68 . Therefore, it is important to discriminate UBC-derived EVs from the heterogeneous population of urinary nontumor-derived EVs, including those produced by the healthy urothelium.…”
Section: Opportunities For Translating Research On Extracellular Vesimentioning
confidence: 99%